The Art and Craftivism of Exhibiting Species and Habitat Loss in Natural History Museums - Sarah Wade (Museum & Society, 2022)
In recent years the presentation of anthropogenic extinction narratives in natural history museums has occurred through temporary exhibitions, curatorial and artistic interventions in permanent collections displays and public engagement events. Such work has enabled institutions to re-orientate historical collections and permanent galleries towards this pressing contemporary issue. This article examines a subset of this wider field of curatorial activity by considering how contemporary handicrafts including knitting and crochet have been displayed to engage visitors with species and habitat loss in natural history museums, situating this work within craftivist practices and the longer history of craft being mobilized for political and ethical ends. While the habitat diorama alerted audiences to disappearing species and threatened ecosystems in the twentieth century through a combination of art, science and craft, I reveal how recent exhibitions and events have reconfigured a similar interdisciplinary mix to raise awareness of species and habitat loss in the twenty-first century.